Energy and transport - Woodcock, J; Banister, D; Edwards, P; Prentice, A; Roberts, I (Elsevier, 2007)
We examine the links between fossil-fuel-based transportation, greenhouse-gas emissions and health. Transport-related carbon emissions are rising and there is increasing consensus that the growth in motorised land vehicles and aviation is incompatible with averting serious climate change. The energy intensity of land transport correlates with its adverse health effects. Adverse health effects occur through climate change, road-traffic injuries, physical inactivity, urban air pollution, energy-related conflict and environmental degradation. For the world's poor people, walking is the main mode of transport, but such populations often experience the most from the harms of energy-intensive transport. New energy sources and improvements in vehicle design and in information technology are necessary but not sufficient to reduce transport-related carbon emissions without accompanying behavioural change. By contrast, active transport has the potential to improve health and equity and reduce emissions. Cities require safe and pleasant environments for active transport with destinations in easy reach and, for longer journeys, public transport that is powered by renewable energy, thus providing high levels of accessibility without car use. Much investment in major road projects does not meet the transport needs of poor people, especially women whose trips are primarily local and off road. Sustainable development is better promoted through improving walking and cycling infrastructures, increasing access to cycles and investment in transport services for essential needs. Our model of London shows how increased active transport could help achieve substantial reductions in emissions by 2030 while improving population health. There exists the potential for a global contraction and convergence in use of fossil-fuel energy for transport to benefit health and achieve sustainability.